Back Cover: New Conjugated Oligothiophenes Containing the Unique Arrangement of Internal Adjacent [All]‐S, S‐Oxygenated Thiophene Fragments (Chem. Eur. J. 17/2013). Issue 17 (12th April 2013) - Potash, Shay; Rozen, Shlomo
<x xml:space="preserve">Abstract</x> Oligothiophenes with inner sulfonated rings were synthesized by using HOF⋅CH3CN, which is easily prepared from diluted F2 and aqueous acetonitrile. This family of compounds exhibits more favorable properties, such as lower HOMO–LUMO gaps and higher reduction potentials, than other fully oxygenated, polyoxygenated, and nonoxygenated oligothiophenes. For more details, see the Full Paper by S. Rozen and S. Potash on p. 5289 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>